Political power and social theory - Go, Julian 1970- (Emerald, 2012)
As economic stagnation freezes the globe; capitalism is increasingly questioned; war, revolution and political instability unsettles the Middle East; and President Obamas campaign for the Presidency looms, Volume 23 of Political Power and Social Theory reflects on these and related issues. Chapters in this volume discuss the meaning of revolution, the origins of neoliberalism in India, identity formation in a Chicago social movement, the Palestinian National Question, and the Black middle-class in the US. Additionally, in the Scholarly Controversy section, Fred Block questions whether the concept of "capitalism" should be problematized entirely.